Minimally Invasive Epicardial Pacemaker Implantation in Neonates with Congenital Heart Block - Costa,Roberto (2017)
Abstract Background: Few studies have characterized the surgical outcomes following epicardial pacemaker implantation in neonates with congenital complete atrioventricular block (CCAVB). Objective: This study sought to assess the long-term outcomes of a minimally invasive epicardial approach using a subxiphoid access for pacemaker implantation in neonates. Methods: Between July 2002 and February 2015, 16 consecutive neonates underwent epicardial pacemaker implantation due to CCAVB. Among these, 12 (75.0%) had congenital heart defects associated with CCAVB. The patients had a mean age of 4.7 ± 5.3 days and nine (56.3%) were female. Bipolar steroid-eluting epicardial leads were implanted in all patients through a minimally invasive subxiphoid approach and fixed on the diaphragmatic ventricular surface. The pulse generator was placed in an epigastric submuscular position. Results: All procedures were successful, with no perioperative complications or early deaths. Mean operating time was 90.2 ± 16.8 minutes. None of the patients displayed pacing or sensing dysfunction, and all parameters remained stable throughout the follow-up period of 4.1 ± 3.9 years. Three children underwent pulse generator replacement due to normal battery depletion at 4.0, 7.2, and 9.0 years of age without the need of ventricular lead replacement. There were two deaths at 12 and 325 days after pacemaker implantation due to bleeding from thrombolytic use and progressive refractory heart failure, respectively. Conclusion: Epicardial pacemaker implantation through a subxiphoid approach in neonates with CCAVB is technically feasible and associated with excellent surgical outcomes and pacing lead longevity.